13 μm emission InAs/AlSb quantum cascade lasers with high slope efficiency and peak output power enabled by diagonal transition design - Rui-Xuan Sun; Shu-Man Liu; Zhe-Yu Song; Jin-Chuan Zhang; Ning Zhuo; Jun-Qi Liu; Li-Jun Wang; Shenqiang Zhai; Feng-Min Cheng; Feng-Qi Liu (AIP Advances, 2024)
Long wavelength InAs/AlSb quantum cascade lasers (QCLs) emitting at 13 μm, based on a diagonal transition scheme design through band structure engineering, have been grown and fabricated. This band structure engineering focuses on enhancing transition efficiency and suppressing carrier leakage. Our 3-mm-long, 25-μm-wide InAs/AlSb QCL has achieved a slope efficiency of 210 mW/A and a maximum peak power of 515 mW, despite encountering a substantial waveguide loss of 27 cm−1 and a relatively high threshold of 4.8 kA/cm2, due to the elevated residual doping level. Our InAs/AlSb QCL devices have demonstrated record-breaking performance in terms of slope efficiency, maximum peak power, and injection efficiency. Cavity length analysis suggests that reducing the residual doping by half could pave the way for achieving continuous wave output power in the realm of hundreds of milliwatts at room temperature for our designed 13 μm QCLs.